Case report of a rare incidentaloma of the adrenal gland—Schwannoma - Usama Muhammad Kathia; Azfar Ali; Ammar Tariq Alvi; Ali Waqar Chaudhry; Hamid Elahi; Khizar Hayat Gondal (Journal of the Pakistan Medical Association, 2023)
The Schwannoma is a benign growth of the nerve sheath cells most commonly seen in the vestibulocochlear nerve. Its prevalence in the adrenal gland is 1-3%. Here we discuss a case that presented as an incidentaloma of the right adrenal gland in a young male patient who had vague abdominal symptoms and a normal hormonal profile. He underwent an excisional biopsy of the right adrenal gland due to the large size of the lesion (more than 4cm). The histopathology report helped to establish the diagnosis of Schwannoma. Incidentaloma is defined as a lesion of the adrenal gland encountered on any radiological investigation carried out for symptoms that are not associated with adrenal pathologies. After discovering such lesions, it is imperative to perform radiological and hormonal investigations in an organised manner to plan further management of such cases. Keywords: Schwannoma, Adrenal Incidentaloma, Adrenocortical Adenoma, Adrenocortical Carcinoma, Adrenalectomy.